PENGARUH KETERAMPILAN MENGAJAR GURU KEWIRAUSAHAAN TERHADAP MOTIVASI BELAJAR SISWA KELAS XI ADP DI SMK MUHAMMADIYAH 2 PEKANBARU - ', Zefron; ', Suarman; ', Gusnardi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the effect of teachers' teaching skills on learning motivation of class XI Adp in Smk Muhammadiyah 2 Pekanbaru. The subject of this research is all students of class XI ADP SMK Muhammadiyah 2 Pekanbaru. Which amounted to 58 people, the sample was taken using Simple Random Sampling technique. The data used are primary data and secondary data with data collection techniques using questionnaire or Questionnaire. Data analysis techniques used are Simple Linear Regression Analysis processed. The results of this study indicate that teachers 'teaching skills have a significant effect on students' learning motivation. This means that the higher the level of a teacher's teaching skills the higher the level of student learning motivation. Thus to improve the motivation to learn is required teaching skills of in his field.Keywords: Teaching Skills, Student Motivation